Calculate (-5)^(-3): Solving Negative Base with Negative Exponent

Question

(5)3=? (-5)^{-3}=\text{?}

Video Solution

Solution Steps

00:00 Solve the following problem
00:02 According to the laws of exponents, a number (A) when raised to the power of (-N)
00:05 equals 1 divided by the number (A) raised to the power of (N)
00:08 Let's apply this to the question, the formula works from number to fraction and vice versa
00:11 We obtain 1 divided by (-5) raised to the power of (3)
00:14 According to the laws of exponents, the number (A*B) raised to the power of (N)
00:17 equals (A) raised to the power of (N) multiplied by (B) raised to the power of (N)
00:20 Let's apply this to the question
00:23 Break down (-5) into factors (-1) and (5)
00:30 We obtain (-1) to the power of 3 multiplied by (5) raised to the power of 3
00:36 Let's solve (-1) raised to the power of 3 according to the laws of exponents
00:51 Let's solve 5 raised to the power of 3 according to the laws of exponents
01:00 This is the solution

Step-by-Step Solution

First let's recall the negative exponent rule:

bn=1bn b^{-n}=\frac{1}{b^n} We'll apply it to the expression we received:

(5)3=1(5)3 (-5)^{-3}=\frac{1}{(-5)^3} Next let's recall the power rule for expressions in parentheses:

(xy)n=xnyn (x\cdot y)^n=x^n\cdot y^n And we'll apply it to the denominator of the expression we received:

1(5)3=1(15)3=1(1)353=1153=153=1125 \frac{1}{(-5)^3}=\frac{1}{(-1\cdot5)^3}=\frac{1}{(-1)^3\cdot5^3}=\frac{1}{-1\cdot5^3}=-\frac{1}{5^3}=-\frac{1}{125} In the first step, we expressed the negative number inside the parentheses in the denominator as a multiplication between a positive number and negative one, and then we used the power rule for expressions in parentheses to expand the parentheses, and then we simplified the expression.

Let's summarize the solution to the problem:

(5)3=1(5)3=153=1125 (-5)^{-3}=\frac{1}{(-5)^3} =\frac{1}{-5^3}=-\frac{1}{125}

Therefore, the correct answer is answer B.

Answer

1125 -\frac{1}{125}